Origins and migratory routes of murine Cajal-Retzius cells. - García-Moreno, F; López-Mascaraque, L; De Carlos, J (2007)
The first layer that appears in the cortical neuroepithelium, the preplate, forms in the upper part of the cortex immediately below the pial surface. In mice, this layer exists between embryonic days (E) 10 and 13, and it hosts different cell populations. Here, we have studied the first cell population generated in the preplate, the Cajal-Retzius cells. There is considerable confusion regarding these cells with respect to both their site of generation and the migratory routes that they follow. This perhaps is due largely to the different opinions that exist regarding their characterization. We have studied the site of origin of these cells, their migratory routes, and the molecular markers that may distinguish them by injecting tracers into early embryos, culturing them in toto for 24 hours, and then performing immunohistochemistry. We found that the Cajal-Retzius cells are most likely generated in the cortical hem by comparing with other cortical or extracortical origins. These cells are generated mainly at E10 and E11, and they subsequently migrate tangentially to cover the whole cortical mantle in 24 hours. From their site of origin in the medial wall of the telencephalon, they spread in a caudorostral direction, following an oblique migratory path toward the lateral part of the neuroepithelium. Prior to the splitting of the preplate, a percentage of the Cajal-Retzius cells that can be distinguished by the expression of reelin do not contain calretinin. Furthermore, there were no early-migrating neurons that expressed calbindin.